An adaptive allocation design for circular treatment outcome. (2nd October 2017) - Biswas, Atanu; Bhattacharya, Rahul; Mukherjee, Taranga
ABSTRACT: A number of allocation designs are developed for continuous and binary treatment outcomes to assign a higher number of subjects to the treatment doing better in course of the trial. However, if the response is circular in nature, the definition of a better treatment differs from that under the linear response and hence the already developed designs lack appropriateness. In the current work, redefining the notions of superiority, we develop an allocation function in the context of circular treatment outcomes. Using a response-adaptive route for practical implementation, we study the resulting design both theoretically and numerically and finally illustrate the performance for a real-life example on cataract surgery.